LIABILITY AGAINST THE INSTALLER COMPANY ADVERTISING THAT HARMS CONSUMERS - Mesya, Arki; Hamzah, Andi (EQUALEGUM International Law Journal, 2023)
Background. Advertising is a means of establishing relationships between companies and consumers. The company tries to communicate well with the existence of the company itself and the products or services produced. The research aimed to explain unlawful acts carried out by advertising companies so that they can cause losses to part of consumers. Research Method. This research uses research methods of normative law, and library research, namely researching library materials or secondary materials. Findings. An unlawful act is any action that brings about such losses. Then there are unlawful acts in Indonesia interpreted broadly, namely covering one of the following actions: (1) Actions that conflict with other people's rights (2) Obligations that conflict with legal obligations (3) Acts that are contrary to morality (4) Acts that are contrary to prudence or necessity in society. Conclusion. Liability for unlawful acts towards advertising companies’ harm to consumers can be resolved through compensation between company advertisers with consumers through District Court.